Contextual Vocabulary Knowledge: the best Predictor of Native and Non-native Speakers’ Reading Comprehension Ability - Khodadady, Ebrahim (The ESPecialist, 2012)
Two hypotheses have been generated to capture the relationship between vocabulary knowledge and reading comprehension ability: instrumental and knowledge. While the former considers contextual vocabulary knowledge, i.e., knowing the meaning of the words used in a text, as the necessary and sufficient condition for comprehending that text, the latter holds it necessary but not sufficient. This study was conducted to test the instrumental hypothesis. The disclosed vocabulary section of the Test of English as a Foreign Language (TOEFL) was adopted as a measure of global vocabulary knowledge, i.e., knowing the meaning of the words unrelated to the text of TOEFL’s reading comprehension section, which was used as a measure of reading comprehension ability. For measuring contextual vocabulary knowledge, another vocabulary test was constructed on the words used in the text of the reading comprehension test. The administration of the contextual vocabulary, global vocabulary, and reading comprehension tests to 64 non-native speakers (NNSs) and 123 native speakers (NSs) showed that although NSs scored significantly higher than NNSs on all tests, the performance of both NNSs and NSs on the contextual vocabulary tests was the best predictor of their performance on the reading comprehension test.